A review of the applications of bioproteins in the preparation of biodegradable films and polymers - Sajad Pirsa; Kurush aghbolagh sharifi (Journal of Chemistry Letters)
Environmental pollution due to the entry of synthetic polymers, plastics and non-degradable packaging materials into nature is one of the greatest dangers that threaten human life. Therefore, in recent years, the use of dietary proteins in the production of biodegradable films has intensified. Protein-based films have attracted a lot of attention because of their advantages, including their ability to be used in a variety of materials packaging. Protein films are used for small food packaging, especially special products such as beans, fruit kernels and cashews. Protein films can also be used to prevent spoilage and moisture migration in foods such as pizza, staples and candies. Protein films have good resistance to the passage of oxygen gas at low relative humidity and have good mechanical properties and turbidity. These films, like synthetic polymers, are used to package food, especially products that are individually packaged, such as beans, nuts, and peanuts. These films can be modified with antimicrobial and antioxidant agents to form bioactive films. Proteins such as corn husk, glutenin and gladin, soy protein, gelatin, collagen, meat myofibril, milk casein, milk whey protein and egg protein are widely used in the production of biodegradable polymers. In this review article, we have tried to study the properties of protein polymers and their applications.